GAYA KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONALITAS GURU MADRASAH TSANAWIYAH BAITURRAHIM KOLAKA - Muhammad Basrul Anwar (UNISAN JURNAL, 2024)
It is hoped that this exploration can determine the authority style of the Madrasah Head in expanding the extraordinary skills of Madrasah Tsanawiyah Baiturrahim Kolaka Educators, Kolaka Mangolo Regency, Kolaka Regency, Southeast Sulawesi. Specialists use subjective exploration strategies. Important sources of information in this examination are the Head of the Madrasah, Educators and Students, while the supporting sources of information come from reports from the madrasah organization. Information gathering strategies Specialists utilize perception, meetings, and documentation. To agree on the information, scientists use the triangulation method. From the explanation that has been carried out well it can be reasoned that: 1). The Duties of Madrasah Heads in Expanding the Amazing Skills of Educators at Madrasah Tsanawiyah Baiturrahim HKSN Kolaka Regency Kolaka Regime Mangolo Kolaka Southeast Sulawesi. The job of the Madrasah Principal is to carry out his obligations with full responsibility and fully intend to develop superior educational skills by implementing regular strategies that can convince or inspire teachers to continue working in accordance with their obligations. each, with abilities in the field of study they cover; 2). The methodology and steps taken by the Head of the Madrasah in developing Impressive Skills for Educators at Madrasah Tsanawiyah Babussalam, Mangolo Kolaka Regency, Southeast Sulawesi is through completing management with an approach of reflection, correspondence, preparation, coordination, assessment, with the implementation at the end. all points and targets will be understood, to further develop the instructor's implementation; 3). Supporting and Emphasizing Elements The task of the Madrasah Head in Organizing the Educator Exhibition at Madrasah Tsanawiyah Babussalam, Mangolo Kolaka Regency, Southeast Sulawesi is to assist all Madrasah Head programs, especially internal and external variables, services and foundations, strategies and projects. This can hinder all forms of movement to further develop the performance of educators and can also hinder any planned actions, so that all parties need to pay attention to carrying out their respective obligations well